Chaca serica, a new species of frogmouth catfish (Teleostei: Siluriformes) from southern Borneo - Ng, Heok Hee; Kottelat, Maurice (Zootaxa, 2012)
Chaca serica, a new species of frogmouth catfish from the Kahayan, Kapuas and Mentaya river drainages in southernBorneo, is described here. It can be distinguished from congeners in having the following combination of characters: theoral margin of the lower lip lacking (vs. having) a series of rugose ridges, presence of nasal barbels, presence of papillaearound the eyes, a temporal fossa extending to the supraoccipital, 7–8 serrae on the anterior edge of the pectoral spine,four pectoral-fin rays, absence of a row of fimbriate skin flaps on the body dorsal to (and sometimes also ventral to) the lateral line, dorsal procurrent caudal-ray base 32.8–37.3% SL, and ventral procurrent caudal-ray base 16.0–19.2% SL.